Hayek, las ciencias y la praxeología - Santoro, Luis Luque (REVISTA PROCESOS DE MERCADO, 2017)
This paper includes the main conclusions driven from a thorough com-pilation and interpretation of F.A. Hayek’s most relevant views on the subjects of philosophy of science, epistemology and methodology regarding social scien-ces. The dialogue that Hayek seems to establish between sciences and methods is particularly highlighted. This dialogue might be summarized in two ways: a «bottom-up» connection, by offering an alternative justification for methodologi-cal dualism and the proper methodological principles for the social sciences, from the perspetive of the natural sciences methodological paradigm in which Hayek frames his human mind theory in his work The Sensory Order; and a «top-down» connection, by concluding with respect to the complex phenomena theo-ries of natural sciences that there exist common methodological challenges with the social sciences, which require in both cases to take into account methodolo-gical differences not covered under the orthodox mainstream methodological paradigm. In this sense an interpretation of Hayek’s methodological approxima-tion to economics as an applied or empirical social science is proposed; which intends to offer explanations about concrete reality, as a necessary complement of Mises praxeology which instead only focuses on pure and formal theory. Keywords: Hayek; Philosophy of Science; Methodology; Praxeology; Pure Logic of Choice. JEL Classification: A12, A14, B41, B53. Resumen: En este trabajo se presentan las principales conclusiones de una detenida compilación e interpretación de los planteamientos más importantes de F.A. Hayek sobre temas de filosofía de la ciencia, epistemología y metodo - logía de las ciencias sociales. En particular se resalta el diálogo que Hayek parece plantear entre ciencias y métodos y que se concretaría en dos senti-dos: en una conexión «por abajo», justificando el dualismo metodológico y los principios metodológicos adecuados para las ciencias sociales, desde el paradigma metodológico de las ciencias naturales en el que elabora su teoría sobre la mente humana en El Orden Sensorial; y en una conexión «por arriba» al concluir respecto a las teorías sobre fenómenos complejos de las ciencias naturales la existencia de retos comunes con los que también se enfrentan las ciencias sociales y que requieren dar cabida en ambos casos a diferencias metodológicas no previstas según el criterio ortodoxo dominante. En este último sentido, se propone una interpretación de la aproximación metodoló-gica de Hayek para la economía como una ciencia social aplicada o empí-rica que tiene como objetivo ofrecer explicaciones de la realidad, como el complemento necesario a la praxeología misesiana centrada en la teoría pura formal. Palabras clave: Hayek; Filosofía de la Ciencia; Metodología; Praxeología; Lógica Pura de la Elección. Clasificación JEL: A12 (Relación de la economía con otras disciplinas); A14 (Sociología de la economía); B41 (Metodología económica); B53 (Escuela aus-triaca).